1998
DOI: 10.1086/515900
|View full text |Cite
|
Sign up to set email alerts
|

The Water Absorption Response: A Behavioral Assay for Physiological Processes in Terrestrial Amphibians

Abstract: Terrestrial amphibians take up water by abducting the hind limbs and pressing a specialized portion of the ventral skin to a moist surface, using a characteristic behavior called the water absorption response. An assay of the water absorption response was used to quantify physiological factors associated with thirst and water uptake. Dramatic changes in the water absorption response resulted from subtle changes in hydration state and from altering the reserve water supply in the urinary bladder. The water abso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(34 citation statements)
references
References 4 publications
0
34
0
Order By: Relevance
“…The tissue electrolyte content was diluted in nonperfused skin, indicating the circulation removed water as it was absorbed to prevent diminution of the osmotic gradient across the epidermis. Water absorption by anurans occurs in conjunction with a behavior, termed the water absorption response (16,26), during which the skin is pressed to a moist surface and there is a large increase in blood flow to the absorbing area of the seat patch (33,34), in conjunction with the insertion of AQPs into the apical membranes of the FRC layer of the skin (27). A better understanding of adaptations for semiterrestrial vs. semiaquatic species will require an understanding of all three parameters from a physiological and phylogenetic perspective.…”
Section: Possible Expression Of New-type Aqps In the Ventral Pelvic Smentioning
confidence: 99%
“…The tissue electrolyte content was diluted in nonperfused skin, indicating the circulation removed water as it was absorbed to prevent diminution of the osmotic gradient across the epidermis. Water absorption by anurans occurs in conjunction with a behavior, termed the water absorption response (16,26), during which the skin is pressed to a moist surface and there is a large increase in blood flow to the absorbing area of the seat patch (33,34), in conjunction with the insertion of AQPs into the apical membranes of the FRC layer of the skin (27). A better understanding of adaptations for semiterrestrial vs. semiaquatic species will require an understanding of all three parameters from a physiological and phylogenetic perspective.…”
Section: Possible Expression Of New-type Aqps In the Ventral Pelvic Smentioning
confidence: 99%
“…The relative importance of these stimuli varies among different classes of vertebrates or among species in different habitats. Thirst motivates oral drinking behavior in terrestrial animals, but it induces cutaneous drinking behavior in amphibians [34]. Angiotensin II is more intimately related to extracellular dehydration because hypovolemia invariably stimulates renin secretion in all of the species examined, while an increase in plasma osmolarity generally inhibits renin secretion in most species examined [35].…”
Section: Thirst Mechanismsmentioning
confidence: 99%
“…Furthermore, angiotensin II seems to induce a sensation of thirst in amphibians. Hillyard and his colleagues [34,47] showed that angiotensin II stimulates water drive in the terrestrial toad, Bufo punctatus; it then induces hind limb abduction to bring a specialized portion of the ventral skin to a moist surface, the so-called "cutaneous drinking behavior." Therefore, it seems that angiotensin II in-Japanese Journal of Physiology Vol.…”
Section: Thirst Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…This chamber also allowed us to evaluate the effect of different immersion levels on BCF and water absorption from deionised water (DI) and salt solutions. Because the toads were conscious and unrestrained, we were able to observe whether the time course for behaviours associated with water absorption (Hillyard et al, 1998) corresponded to the physiological response to water contact (increase in BCF).…”
Section: Introductionmentioning
confidence: 99%